2013
DOI: 10.1007/s10858-013-9740-z
|View full text |Cite
|
Sign up to set email alerts
|

Fragment-based drug discovery using NMR spectroscopy

Abstract: Nuclear magnetic resonance (NMR) spectroscopy has evolved into a powerful tool for fragment-based drug discovery over the last two decades. While NMR has been traditionally used to elucidate the three-dimensional structures and dynamics of biomacromolecules and their interactions, it can also be a very valuable tool for the reliable identification of small molecules that bind to proteins and for hit-to-lead optimization. Here, we describe the use of NMR spectroscopy as a method for fragment-based drug discover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
195
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 188 publications
(196 citation statements)
references
References 77 publications
0
195
0
1
Order By: Relevance
“…Notably, the 34 kDa CXCR1 chemokine G protein-coupled receptor (GPCR) structure was elucidated by rotationally aligned (RA) solid-state NMR [21]. NMR also has an important role to play in investigating protein-protein, and ligand-protein interactions as well as for fragment-based drug discovery [24][25][26].…”
Section: Nmrmentioning
confidence: 99%
“…Notably, the 34 kDa CXCR1 chemokine G protein-coupled receptor (GPCR) structure was elucidated by rotationally aligned (RA) solid-state NMR [21]. NMR also has an important role to play in investigating protein-protein, and ligand-protein interactions as well as for fragment-based drug discovery [24][25][26].…”
Section: Nmrmentioning
confidence: 99%
“…[2] However,t argeting PPIs can be difficult owing to their large hydrophobic binding surfaces. [3] There are currently three commonly employed approaches to develop modulators of PPIs: [4] fragment screening, [5] computational screening and drug design, [6] and the exploration of peptides and peptidomimetics. [7] However,c omputational design and fragment screening require large libraries of molecules and extensive synthetic work, often resulting in non-selective compounds.…”
Section: Protein-proteininteractions(ppis)regulatemanyprocessesmentioning
confidence: 99%
“…This has given rise to increased interest in fragment screening and then fragmentbased drug design (FBDD), in which the molecules screened generally conform to the Rule of 3 rather than the well-known Rule of 5. 18 These fragment molecules are generally below molecular weight 300 Da, with a calculated partition coefficient clogP <3 and less than 3 hydrogen bond donors. The advantages of using fragments are that (i) fragment chemical space is much much smaller than drug space because of the smaller molecular size and it can thus be covered more completely with a reasonably sized library, (ii) fragments tend to be more promiscuous in their binding than larger molecules because they are unencumbered with lots of side chains and appendages that get in the way of a good binding interaction, and (iii) there is a perception that the ligand efficiency (binding energy per heavy atom) of fragments is higher than that of conventional, larger ligands, although in our experience that is not always the case.…”
Section: New Applications Of Nmr Spectroscopy In Pharmaceutical Randdmentioning
confidence: 99%
“…Utilizing fast pulsing methods, it has been reported that more than 200 2-D heteronuclear correlation NMR spectra can be recorded in 24 h using a 500 MHz NMR spectrometer with a cryoprobe, 40 μM protein concentration and a relatively small, globular protein of 15 kDa. 18 These general methods can also be applied to the study of protein-carbohydrate interactions 19 and to the study of complexes with membrane proteins 20 ( Figure 6). This is an exciting and important area, and the first drug emerging from a fragment-based drug discovery approach, Vemurafenib (Figure 7), was approved in 2011.…”
Section: New Applications Of Nmr Spectroscopy In Pharmaceutical Randdmentioning
confidence: 99%